Multi-Omics Characterization of Host-Derived Bacillus spp. Probiotics for Improved Growth Performance in Poultry - Susanti, Dwi; Volland, Alyssa; Tawari, Nilesh; Baxter, Nielson; Gangaiah, Dharanesh; Plata, Germán; Nagireddy, Akshitha; Hawkins, Troy; Mane, Shrinivasrao P.; Kumar, Arvind (Frontiers in Microbiology, 2021)
Microbial feed ingredients or probiotics have been used widely in the poultry industry to improve production efficiency. Spore-forming Bacillus spp. offer advantages over traditional probiotic strains as Bacillus spores are resilient to high temperature, acidic pH, and desiccation. This results in increased strain viability during manufacturing and feed-pelleting processes, extended product shelf-life, and increased stability within the animal’s gastrointestinal tract. Despite numerous reports on the use of Bacillus spores as feed additives, detailed characterizations of Bacillus probiotic strains are typically not published. Insufficient characterizations can lead to misidentification of probiotic strains in product labels, and the potential application of strains carrying virulence factors, toxins, antibiotic resistance, or toxic metabolites. Hence, it is critical to characterize in detail the genomic and phenotypic properties of these strains to screen out undesirable properties and to tie individual traits to clinical outcomes and possible mechanisms. Here, we report a screening workflow and comprehensive multi-omics characterization of Bacillus spp. for use in broiler chickens. Host-derived Bacillus strains were isolated and screened for desirable probiotic properties. The phenotypic, genomic and metabolomic analyses of three probiotic candidates, two B. amyloliquefaciens (Ba ATCC PTA126784 and ATCC PTA126785), and a B. subtilis (Bs ATCC PTA126786), showed that all three strains had promising probiotic traits and safety profiles. Inclusion of Ba ATCC PTA12684 (Ba-PTA84) in the feed of broiler chickens resulted in improved growth performance, as shown by a significantly improved feed conversion ratio (3.3%), increased of European Broiler Index (6.2%), and increased average daily gain (3.5%). Comparison of the cecal microbiomes from Ba PTA84-treated and control animals suggested minimal differences in microbiome structure, indicating that the observed growth promotion presumably was not mediated by modulation of cecal microbiome.